Learning Innovation through Game-Based Learning Assisted by Wordwall Media on Elementary School Students’ Numeracy Skills: Inovasi Pembelajaran melalui Game Based Learning berbantuan Media Wordwall terhadap Kemampuan Numerasi Siswa Sekolah Dasar - Sulaiman Sulaiman; Sumiyati Sumiyati; Arifin Arifin; Nurjannah Nurjannah (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2025)
This study investigates the effectiveness of the Game Based Learning model assisted by Wordwall in improving elementary school students’ numeracy skills. The research was motivated by the low achievement of numeracy competencies in mathematics, which hinders students’ ability to apply concepts functionally. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed involving 14 fifth-grade students. Data were analyzed using validity and reliability testing, normality and linearity tests, paired-sample t-test, and N-Gain analysis. Results indicated an increase in the average numeracy score from 62.42 (pretest) to 72.14 (posttest), with a significance value of 0.000 (<0.05). The N-Gain score of 0.53 categorized the improvement as moderate. These findings confirm that Game Based Learning assisted by Wordwall is effective in enhancing students’ numeracy performance and can be considered as an innovative instructional strategy in mathematics learning at the elementary level.